2004
DOI: 10.21273/hortsci.39.5.917
|View full text |Cite
|
Sign up to set email alerts
|

The Schroeder Institute in Uzbekistan: Breeding and Germplasm Collections

Abstract: on tree fruits; grapes (Vitis vinifera L.); various vegetables; fi ber crops, such as cotton (Gossypium hirsutum L. and G. barbadense L.), kenaf (Hibiscus cannabinus L.), and hemp; (Cannabis sativa L.), rice (Oryza sativa L.), cereal crops, and forage crops. Later, separate research institutes were established to focus on individual crops and initiate specifi c breeding programs. TAES was the fi rst institute in Central Asia established for studies of genetics/breeding and the cultural management of fruits, gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
26
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
4
2
1

Relationship

3
4

Authors

Journals

citations
Cited by 18 publications
(26 citation statements)
references
References 0 publications
0
26
0
Order By: Relevance
“…In Uzbekistan, a significant portion of almonds is grown in Tashkent, Surkhandarya, and Samarkand Provinces and in the Ferghana Valley, which spans adjacent regions of Uzbekistan, Tajikistan, and Kyrgyzstan. The total land area of almonds in Uzbekistan is more than 2500 ha with 1000 ha being cultivated (Mirzaev et al, 2004). The FAO estimated that 2012 almond production (area harvested) in Uzbekistan was 6400 ha (FAOSTAT, 2014).…”
Section: Distribution and Cultivation Of Almond In The Former Ussrmentioning
confidence: 99%
“…In Uzbekistan, a significant portion of almonds is grown in Tashkent, Surkhandarya, and Samarkand Provinces and in the Ferghana Valley, which spans adjacent regions of Uzbekistan, Tajikistan, and Kyrgyzstan. The total land area of almonds in Uzbekistan is more than 2500 ha with 1000 ha being cultivated (Mirzaev et al, 2004). The FAO estimated that 2012 almond production (area harvested) in Uzbekistan was 6400 ha (FAOSTAT, 2014).…”
Section: Distribution and Cultivation Of Almond In The Former Ussrmentioning
confidence: 99%
“…In general, apricot trees start producing fruit at 3 to 4 years when grafted and 4 to 5 years when grown from seed. Depending on the cultivar, the average yield is generally 10 to 15 t • ha -1 (Mavlyanova et al, 2005;Mirzaev et al, 2004). The average productivity of a cultivated apricot is 80 to 100 kg per tree, but exceptional trees can yield 500 to 600 kg with some reports of up 1100 kg per tree (Pulatov, 1976).…”
Section: Morphology and Biology Of P Armeniaca In Central Asiamentioning
confidence: 99%
“…Although PPV strain D was detected in both plum and apricot trees there, it was reported that the plum displayed severe leaf symptoms, whereas only a single apricot tree showed obvious symptoms. Uzbekistan, Tajikistan, Kyrgyzstan, and Turkmenistan still appear to be free of the virus (S. Kozubaev (Mirzaev et al, 2004). Since 1928, the Uzbek Scientific Research Institute of Plant Industry has maintained a living collection of 650 apricot cultivars originating from different geographical regions (Mavlyanova et al, 2005;Smirnova, 1980).…”
Section: Plum Pox Virusmentioning
confidence: 99%
See 1 more Smart Citation
“…In Uzbekistan, pistachio research is currently being conducted at the Shroeder Uzbek Research Institute of Fruit Growing, Viticulture, and Wine Production (Mirzaev et al 2003); The Uzbek Scientific Research Institute of Plant Industry (Mavlyanova et al 2005); Tashkent State Agrarian University; and the Republican Scientific Center for the Production of Ornamental Plants and Forest Management. The first germplasm collection was planted in 1976 at the Sarikurgan Forestry Farm in the Nurata Range of Samarqand Province.…”
Section: Research and Germplasm Holdings Of P Vera In Central Asiamentioning
confidence: 99%